Bahasa Arab dan Problematika Pembelajarannya - Abdul Rohman (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2022)
There are some factors influencing teaching and learning in Indinesia of foreign language, In teaching Arabic, Arabic is one of the most vocabulary languages and is among the most complicated to learn. So in learning Arabic there are often many obstacles and problems faced by the learner. Problem of learning the Arabic language is the problem of certain elements of the inhibition process of learning the Arabic language, the problem of learning the Arabic language consists of linguistic problems of governance that includes sounds / Phonetik, vocabulary, writing, morphology, syntax and semantics, the problem of non-linguistic include: socio kultural, materials, facilities, instructional media, teacher competence, interests of students, and others.